Kredibilitas Informasi Bidang Kesehatan yang Diperoleh Mahasiswa Fakultas Kedokteran Universitas Andalas dari Internet - Maharani, Sistyan; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
The purpose of this study is to describe how the students of Faculty of Medicine, Andalas University determine the credibility of health information retrieved from the Internet. Data was collected through observation and interviews toward the Faculty of Medicine students. Data was analyzing descriptively. The findings of the research is a few criteria to determine the information credibility, such as (1) appearance, (2) the author, (3) the numbers of advertising and, (4) affiliate institutions. It is suggested additional criteria to determine the credibility of health information, those are (1) notify the E-health field, (2) compare the information on the internet to information in printed books. Keywords: information; health information; internet; credibility